UNCONSCIOUS MOTIVES OF THE MAIN CHARACTER AS REFLECTED IN “STRAW” MOVIE: A PSYCHOLOGICAL APPROACH: English - Mariaty Febriany (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2026)
The purpose of this study was to analyze the unconscious motives of the main character, Janiyah, in the movie Straw (2025) using Sigmund Freud’s psychoanalytic theory (1923). This research applied a descriptive qualitative approach by examining selected dialogues and scenes that reflected the character’s psychological experiences. The study focused on how traumatic events stored in the subconscious mind influenced hallucinations, forced violent behavior, and changes in mental state. The findings showed that Janiyah’s hallucinations were caused by severe trauma, including the loss of her child, pressure from authority figures, feelings of helplessness, and accumulated stress. The study also revealed that the act of killing committed by the character was not intentional but was forced by extreme life conditions such as job loss, loss of shelter, and threatening situations. Furthermore, the research found that these traumatic experiences significantly affected Janiyah’s mental state, leading to shock, emotional breakdown, paranoia, loss of self-control, and disorientation. These conditions indicated the use of defense mechanisms such as repression, projection, displacement, and dissociation. Overall, the study concluded that Straw (2025) portrayed how unresolved trauma and subconscious processes distorted perception and behavior. This research confirmed that Freud’s psychoanalytic theory was useful in explaining trauma-related hallucinations, defense mechanisms, and psychological breakdown in contemporary film.